Adaptive inertia emulation control for high‐speed flywheel energy storage systems. Issue 22 (15th October 2020) - Karrari, Shahab; Baghaee, Hamid Reza; Carne, Giovanni De; Noe, Mathias; Geisbuesch, Joern
Abstract : Low‐inertia power systems suffer from a high rate of change of frequency (ROCOF) during a sudden imbalance in supply and demand. Inertia emulation techniques using storage systems, such as flywheel energy storage systems (FESSs), can help to reduce the ROCOF by rapidly providing the needed power to balance the grid. In this work, a new adaptive controller for inertia emulation using high‐speed FESS is proposed. The controller inertia and damping coefficients vary using a combination of bang–bang control approaches and self‐adaptive ones, to simultaneously improve both the ROCOF and the frequency nadir. The performance of the proposed adaptive controller has been initially validated and compared with several existing adaptive controllers by means of offline simulations, and then validated with experimental results. The proposed controller has been implemented on a real 60 kW high‐speed FESS, and its performance has been evaluated by means of power hardware‐in‐the‐loop (PHIL) testing of the FESS in realistic grid conditions. Both simulations and PHIL testing results confirm that the proposed inertia emulation control for the FESS outperforms several previously reported controllers, in terms of reducing the maximum ROCOF and improving the frequency nadir during large disturbances.